Pengaruh Infrastruktur Pelabuhan terhadap Manajemen Risiko dan Efektivitas Logistik - Luthfiyah, Haura (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to analyze in depth the effect of port infrastructure on these two aspects aspects. This evaluation will involve an assessment of the factors port infrastructure that affect risk management and logistics efficiency, including facilities, technology, and operational procedures. In addition, the research aims to further explore how port infrastructure modernization and effective risk management port infrastructure and effective risk management practices can contribute to improved service quality and long-term budget sustainability. long-term budget sustainability. Methods This research uses a literature study approach to examine the influence of port infrastructure on risk management and logistics effectiveness. Data were collected through searching electronic databases such as Scopus and JSTOR with specific keywords, as well as systematic review to ensure the quality and relevance of sources. Content analysis was conducted to identify key themes, followed by thematic analysis to categorize the findings. The synthesis of data from these various sources will assist in drawing conclusions that answer the research questions and provide evidence-based recommendations for port infrastructure development in Indonesia. The results show that adequate and modern port infrastructure contributes significantly to improved risk management and logistics efficiency. Investments in port infrastructure support sustainable economic growth and strengthen the maritime logistics sector. The research provides recommendations for the development of resilient and adaptive port strategies, which are important for stakeholders in responding to global and regional changes. The main conclusion is that reliable port infrastructure improves the reliability and safety of freight shipments, strengthens the port's position as a global logistics hub, and is a strategic investment for a safer and more efficient logistics future.